2022
DOI: 10.1016/j.gfj.2021.100635
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of fraud and overcoming negative market reaction

Abstract: Consequences of Fraud and Overcoming NegativeMarket Reaction and submitted in partial fulfillment of the requirements for the degree of Master of Science (Administration)Complies with the regulations of the University and meets the accepted standards with respect to originality and quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The research contributions of this study are summarized in the following: Firstly, we creatively investigate corporate CSR disclosure strategy affected by administrative penalties from the perspective of impression management. Most of the existing literature explores the remedial measures taken by firms after administrative penalties from the perspective of internal governance mechanisms such as changes in supervisory personnel and frequency of meetings (Cianci et al, 2019; Karajian & Ullah, 2021). Distinguished from those studies, we focus on the impact of administrative penalties on the use of pictures and tables in CSR reports as disclosure strategies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research contributions of this study are summarized in the following: Firstly, we creatively investigate corporate CSR disclosure strategy affected by administrative penalties from the perspective of impression management. Most of the existing literature explores the remedial measures taken by firms after administrative penalties from the perspective of internal governance mechanisms such as changes in supervisory personnel and frequency of meetings (Cianci et al, 2019; Karajian & Ullah, 2021). Distinguished from those studies, we focus on the impact of administrative penalties on the use of pictures and tables in CSR reports as disclosure strategies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that in firms subjected to administrative penalties, executives face risks such as salary reductions and demotions (Conyon & He, 2016). Consequently, administrative penalties manifestly exert negative influences on firms that motivate them to implement remedial measures aimed at rebuilding trust among stakeholders and mitigating the negative repercussions of penalties (Cianci et al, 2019 Farber, 2005; Karajian & Ullah, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulations can affect several organisations' legitimacy and impact innovation, entrepreneurship, regulatory compliance, society, and the economy (Belas et al, 2015). Karajan and Ullah (2022) investigated how disclosing the company's accounting manipulations affects the company's profitability. They found that the earnings of these companies were a significant decrease.…”
Section: Accounting Manipulationsmentioning
confidence: 99%